2022
DOI: 10.3389/fpubh.2022.1009164
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning and natural language processing for predicting stroke-associated pneumonia

Abstract: BackgroundIdentifying patients at high risk of stroke-associated pneumonia (SAP) may permit targeting potential interventions to reduce its incidence. We aimed to explore the functionality of machine learning (ML) and natural language processing techniques on structured data and unstructured clinical text to predict SAP by comparing it to conventional risk scores.MethodsLinked data between a hospital stroke registry and a deidentified research-based database including electronic health records and administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Furthermore, much data remain to be mined. Tsai et al [ 18 ] found that information extracted from unstructured clinical text could make predictive models more comprehensive and improve their predictive performance. In addition to unstructured clinical text, lung radiography and computed tomography can be used to predict the occurrence of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, much data remain to be mined. Tsai et al [ 18 ] found that information extracted from unstructured clinical text could make predictive models more comprehensive and improve their predictive performance. In addition to unstructured clinical text, lung radiography and computed tomography can be used to predict the occurrence of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…While previous research has explored the immediate risk of stroke in dizzy patients, this study uniquely investigated long-term stroke risk and types of strokes post-ED discharge. Moreover, this study utilized data from the DRD, a hospital research-based database containing long-term and varied healthcare data for a large patient population [ 18 ]. The comprehensive nature of the DRD further enhanced the study's capability to capture and analyze relevant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The study data were extracted from the Ditmanson Research Database (DRD), a deidentified research-based database containing administrative claims data, electronic medical records, and vital status information provided by the National Death Index. The details of the DRD have been described elsewhere [ 18 ]. Briefly, the DRD holds clinical information for approximately 1.6 million patients who visited the study hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Another comparative study concluded that the clinical prediction scores varied in their simplicity of use and, while comparable in performance, their utility for preventive intervention trials and in clinical practice required further investigation [ 21 ]. More recently, ML-based prediction of SAP, including methods based on natural language processing, has also been explored [ 17 , 18 ]. These studies reported AUCs of 0.84 which is below the AUC of 0.91 reported here.…”
Section: Discussionmentioning
confidence: 99%